Exploring the causal effects of serum lipids and lipidomes on lewy body dementia: a Mendelian randomization study - Fu, Qingan; Pan, Guanrui; Yu, Qingyun; Liu, Zhekang; Shen, Tianzhou; Ma, Xiaowei; Jiang, Long (Frontiers in Endocrinology, 2024)
Background Lewy body dementia (LBD) is a neurodegenerative disorder characterized by the accumulation of Lewy bodies, which primarily composed of misfolded alpha-synuclein (αS). The development of LBD and APOE4 subtypes is thought to be associated with disorders of lipid metabolism. In this study, we investigated the causal relationship between serum lipids, liposomes and LBD using a two-sample Mendelian randomization (TSMR) method. Methods A TSMR analysis of genome-wide association study (GWAS) data for 8 serum lipids, 179 lipidomes components, LBD and its subtypes was performed, using inverse variance weighted as the primary outcome. To ensure robustness, the sensitivity analyses including MR Pleiotropy RESidual Sum and Outlier, Cochran’s test, leave-one-out method and funnel plots were performed. Results In this study, we found that low-density lipoprotein cholesterol (LDL-C) (OR=1.45, 95% CI=1.19-1.77, P<0.001) and remnant cholesterol (RC) (OR=2.64, 95% CI=1.64-4.28, P<0.001) had significant positive causal effects on LBD, and RC also had a positive effect on LBD in carriers of the APOE4 gene. The results of lipidome analysis showed that phosphatidylcholine (PC) (O-16:0_20:4) levels (OR=0.86, 95% CI=0.75-0.98, P=0.02) and PC (O-18:1_20:4) levels (OR=0.76, 95% CI=0.65-0.89, P <0.001) had negative causal effects on LBD, whereas phosphatidylinositol (PI) (18:1_20:4) levels had a positive causal effect on LBD (OR=1.19, 95% CI=1.02-1.39, P=0.03). For LBD with APOE4 carriers, high levels of PC (16:1_18:0) and PC (O-18:2_18:1) had a significant positive effect, while high levels of PC (O-16:1_18:0), phosphatidylethanolamine (PE) (O-18:2_18:1), sphingomyelin (SM) (d38:2), and triacylglycerol (TAG) (56:5) significantly reduced the risk. No heterogeneity and horizontal pleiotropy were observed in sensitivity analysis. Conclusion Elevated LDL-C and RC levels are significant risk factors for LBD, with RC also impacting APOE4-carrying LBD. Glycerophospholipids play a crucial role in the pathogenesis of LBD, but the specific components that play a role differ from those with the APOE4 carries. These findings highlight the importance of lipid metabolism in LBD and APOE4 subtypes.